Development of compliance theory based on self-regulation in chronic kidney failure patients on hemodialysis - Melastuti, Erna; Nursalam, Nursalam; Sukartini, Tintin; Priyantini, Diah (International Journal of Public Health Science (IJPHS), 2024)
Self-management in regulating diet, fluids, activities, and medication in chronic renal failure patients which getting hemodialysis is still worse. This research aimed to develop the theory of compliance based on self-regulation to increase patient obedience and awareness. A cross-sectional approach of 130 respondents was recruited using simple random sampling. Structural equation modeling partial least square (SEM-PLS) was the statistical analysis for this study. All indicators in the outer model showed outer loading value >0.7, it declared feasible to predict each of the latent variables. The R-square value of appraisal latent was 0.576, Coping was 0.897, and self-care compliance was 0.713. The model was relevant when applied in other research studies with a Q-Square value=0.832. The goodness of fit (GoF) was 0.832>0.36, which means that the model was applied well. The appraisal variable is the strongest variable that influences coping, based on the hypothesis test. The self-regulation-based compliance model for blood pressure, interdialytic weight gain (IDWG), sodium levels, and functional independence can be developed through analysis of the structural model.